Feeding preference of the shredder Phylloicus sp. for plant leaves of Chrysophyllum oliviforme or Miconia chartacea after conditioning in streams from different biomes - Reis,D. F. (2019)
Abstract Macroinvertebrate shredders consume preferably leaves conditioned by fungi and bacteria which offer greater palatability to them. Plant species in Cerrado present high concentration of chemical elements such as lignin and cellulose, phenols and tanins thus making them less attractive for shredders consumption and limiting the palatability. This study aimed to evaluate the feeding preference of a macroinvertebrate shredder of the genus Phylloicus for plant material from two different biomes (Cerrado and Mata Atlântica), after conditioning in a stream of Mata Atlântica and observing their physical and chemical characteristics. Senescent leaves were collected, monthly from the litterfall of riparian vegetation in a 500 m stretch of a stream in each biome from August 2014 to January 201. The most abundant species in each stream was selected for the experiment. The experimental design consisted in with two treatments. The first (T1) comprised leaf discs from Chrysophyllum oliviforme (Cerrado species) together with leaf discs of Miconia chartacea (Atlantic Forest species) which were conditioned in the Atlantic Forest stream. The second treatment (T2) involved leaf discs of Miconia chartacea conditioned in Mata Altlântica and Cerrado streams. Both tests had showed significant differences between the two treatments (T1 and T2). For T1, there was consumption of M. chartacea leaf discs by Phylloicus sp., but there was no consumption of C. oliviforme discs. For T2, there was preference for M. chartaceae leaves conditioned in a stream of Mata Atlântica than in Cerrado stream. The results showed that Phylloicus sp., had presented preference for food detritus of the Mata Antlântica biome and rejection to the one from Cerrado biome.